SPEECH ACT IN AN INDONESIAN TELEVISION TALK SHOW (CONTENT ANALYSIS RESEARCH IN MATA NAJWA TALK SHOW AT METRO TV) - Tressyalina, T; Ridwan, Sakura (INTERNATIONAL JOURNAL OF LANGUAGE EDUCATION AND CULTURE REVIEW, 2015)
The objective of this research was to understand comprehensively about implementation of direct and indirect speech act in Mata Najwa talk shows on Metro TV. It was a qualitative research with content analysis method. The data were collected through indirect participant using observation and some document study were video recordings of audio-visual from www.matanajwa.com pages. It was started of January 2014 to March 2014. The analysis and interpretation of data, indicated that direct speech act mode was more dominant than indirect speech act. Direct speech act was conducted through speech of interrogative, declarative, and imperative. Indirect speech act was conducted through speech of declarative and interrogative for imperative mode.